China’s Experience in Corporate Governance: The Role of Supervision Mechanisms in the Company Law - Tiankun Li (Studies in Law and Justice, 2024)
Improving corporate governance structures is the primary objective of the amendments to China’s Company Law, with a central focus on adjusting existing corporate supervision mechanisms. Building upon the current supervisory board system, the amended Company Law introduces the audit committee under the board of directors, representing a significant institutional innovation as it transitions from a dual-tier to a single-tier governance framework. The supervisory board has been redefined from a mandatory to an optional institution, affirming the flexibility and openness in the configuration of supervisory mechanisms. As a functional alternative to the supervisory board, the audit committee shares certain financial oversight responsibilities but differs in its emphasis. In the process of regulatory adjustments, the specific scope of statutory duties should be further clarified, and the proportion of non-executive directors appropriately increased. The ultimate goal of effective corporate governance lies in balancing the interplay between supervision and management. Therefore, the construction of supervisory mechanisms should be tailored to China’s corporate governance practices and local conditions.